Abjection and the Melancholic Imagination: Towards a Poststructuralist Psychoanalytic Reading of Blake’s The Book of Urizen - Buchsbaum, Julianne (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2009)
Julia Kristeva’s work on the semiotic and the symbolic seems particularly relevant to Blake’s poem The Book of Urizen insofar as she is concerned with how we develop as speaking beings and how language both disguises and reveals evidence of a previous state of union with what she calls the maternal chora. These ideas allow for an interesting reading of Blake’s concern with the splitting off of Urizen from the Eternals and how this splitting off enables him to emerge as a signifying subject who bears traces of traumatic loss and upheaval, or of what Kristeva would term “the abject.” Abjection is a key concept for Kristeva and plays an essential role in what she describes as the “melancholic imagination.” Abjection in Urizen manifests as a sort of paranoid repression and repudiation of the drives, of mutability, multiplicity, the body, and the Other. Urizen, throughout the poem, becomes overtly identified with the Symbolic Father and becomes himself the bearer of symbolic codes, legislator of rational discourse and semantic meaning.